Уточнение гипотезы Фойгта применительно к меди и латуни; Вестник машиностроения; № 6 - Томилин А. К. Александр Константинович; Кузнецов Ф. Ю. Федор Юрьевич; Коноваленко И. С. Иван Сергеевич; Коноваленко И. С. Игорь Сергеевич (2022, 2022)
Заглавие с экрана